2015
DOI: 10.1088/0143-0807/37/1/015501
|View full text |Cite
|
Sign up to set email alerts
|

Zipper model for the melting of thin films

Abstract: We propose an alternative model to Lindemann's criterion for melting that explains the melting of thin films on the basis of a molecular zipper-like mechanism. Using this model, a unique criterion for melting is obtained. We compared the results of the proposed model with experimental data of melting points and heat of fusion for many materials and obtained interesting results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…During the graphene synthesis using PECVD, the patterns are well maintained even when the temperature rises up to 900 °C, as shown in figures 2(b) and (c). We carefully selected the optimum thickness of the Cu film for the synthesis of graphene in order to prevent structural deformation of patterns, because the melting point of Cu film becomes lower than that of bulk Cu [35,36]. The surface roughness of deposited Cu film increases after the synthesis of graphene using PECVD when compared to that of the asdeposited Cu film.…”
Section: Resultsmentioning
confidence: 99%
“…During the graphene synthesis using PECVD, the patterns are well maintained even when the temperature rises up to 900 °C, as shown in figures 2(b) and (c). We carefully selected the optimum thickness of the Cu film for the synthesis of graphene in order to prevent structural deformation of patterns, because the melting point of Cu film becomes lower than that of bulk Cu [35,36]. The surface roughness of deposited Cu film increases after the synthesis of graphene using PECVD when compared to that of the asdeposited Cu film.…”
Section: Resultsmentioning
confidence: 99%
“…Previous ADI-MS work with the microplasma showed that temperatures as high as 300 °C can be realized on glass substrates. 20 This level of thermal energy may well be sufficient to vaporize solution residue samples and thin (≤100 nm) metallic films 28,29 but is not high enough to vaporize bulk metals. Because the LS-APGD is sustained with a flow of 5% HNO 3 , acid dissolution could be important.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The final mass (177 ± 1 ng) corresponds to a mass loss of 33.6%. This mass loss indicates that CuSO 4 •5H 2 O dehydrates completely and also reduced finally to Cu 2 O following these reaction steps [48].…”
Section: Tg With Cuso 4 •5h 2 O Crystalsmentioning
confidence: 94%
“…We associate the current value at which the microheater fails to the melting temperature of platinum (1768 °C). The melting point of thin films for a thickness >50 nm is equivalent to the bulk values [47,48]. We took the melting temperature and the corresponding power that led to failure of the heater as one calibration point (burn-through), and room temperature as second calibration point.…”
Section: Microheatermentioning
confidence: 99%